Reliability of Muscle Oxygen Saturation for Evaluating Exercise Intensity and Knee Joint Load Indicators - Aldo A. Vasquez-Bonilla; Rodrigo Yáñez-Sepúlveda; Matías Monsalves-Álvarez; Marcelo Tuesta; Daniel Duclos-Bastías; Guillermo Cortés-Roco; Jorge Olivares-Arancibia; Eduardo Guzmán-Muñoz; José Francisco López-Gil (Journal of Functional Morphology and Kinesiology)
Objectives: This study aimed to evaluate the reliability of muscle oxygen saturation (SmO2) and its correlation with variables from an inertial measurement unit (IMU) sensor placed on the knee at different exercise intensities. Methods: Fourteen university athletes participated in the study. Incremental ergospirometry was performed to exhaustion to calculate V’O2max, determine training zones, heart rate, and workload using the IMU, and analyze muscle metabolism by SmO2. Results: The analysis revealed significant differences between moderate-to-high-intensity zones (80–89% vs. 50–69%, Δ = 27% of SmO2; p < 0.001) and high-intensity zones (90–100% vs. 50–79%, Δ = 35% of SmO2; p < 0.001). SmO2 values showed moderate reliability at moderate exercise intensities (e.g., ICC 0.744 at 50%) and high variability at higher intensities, with ICC values around 0.577–0.594, and CV% increasing up to 77.7% at 100% intensity, indicating decreasing consistency as exercise intensity increases. SmO2 significantly decreases with increasing angular velocity (β = −13.9, p < 0.001), while knee joint load only shows significant correlations with SmO2 in the moderate-to-high-intensity zones (r = 0.569, p = 0.004) and high-intensity zones (r = 0.455, p = 0.012). Conclusions: SmO2 is a key predictor of performance during maximal incremental exercise, particularly in high-intensity zones. Moreover, SmO2 has the potential to serve as a physiological marker of the internal load on the muscles surrounding the knee during exercise. The SmO2 decrease could depend on the angular velocity and impact of the exposed knee during running.